Analisis Yuridis Pemilik Manfaat Yayasan Berdasarkan Peraturan Presiden Nomor 13 Tahun 2018 - Moerdany, Vira; Prija Djatmika; Hanif Nur Widhiyanti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This thesis aims to analyze the legal conflict between the foundation law and Presidential Regulation Number 13 of 2018 concerning beneficial owners in foundations, where foundations shouldn’t have a beneficial owner. The issues raised are: (1) What’s the juridical analysis of the Criteria for Beneficial Owners of Foundations based on Article 5 of Presidential Regulation Number 13 of 2018 from the perspective of the Foundation Law? and (2) What’s the legal certainty regarding Notaries obligations in listing the beneficial owners in the process of ratifying, establishing or changing the foundation's legal entity, based on Minister of Law and Human Rights Regulation Number 9 of 2017? Research methods used are statute approach and conceptual approach. Resulting in a conclusion that a foundation doesn’t have a beneficial owner, and legal certainty for notaries remains uncertain. Therefore, this Presidential Decree should be created and aimed at corporations formed as companies, with profit-oriented activities.